Chaucer and language : essays in honour of Douglas Wurtele - Myles, Robert, 1947-; Williams, David (David Eliot), 1939-; Wurtele, Douglas J. (Douglas James) (McGill-Queen's University Press, 2001)
Geoffrey Chaucer is increasingly recognized as a writer whose work is particularly congenial to modern tastes. The essays in Chaucer and Language are at the forefront of present-day interest in Chaucer as a highly self-conscious manipulator of language and theorist of signification in the broadest sense.